PENGARUH METODE SOSIODRAMA TERHADAP KEMAMPUAN MENENTUKAN UNSUR INTRINSIK CERPEN SISWA SEKOLAH DASAR (Studi Eksperimen Kuasi Siswa Kelas V SD Negeri 184 Pekanbaru) - Wulan Sucitra; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of factor that influence low capacity of determining the intrinsic elements of the short story is during the learning process of students is less interaction and difficult to understand the subject matter. That’s why the author need to did the research by sociodrama method. The learning method is capable of making active students in developing science and involve the students as a whole, provide the opportunity for students to acquire and understand knowledge directly, as well as the learning process becomes memorable and long lasting in the minds of students so as to improve the ability of determining intrinsic elements short story. The main objective of this study is to determine how much influence sociodrama method to the abality of determining intrinsic elements short storystudents at class V of SD Negeri 184 Pekanbaru. This research was conducted SDN 184 Pekanbaru in class Vb as the control class and class Va as the experimental class using randomized pretest-posttest control group design. Based on the results of Wilcoxon Signed Rank Test with significance level α = 0.05, pvalue (Asymp. Sig. 2-tailed) 0.024 <0.05. The results this study is application sociodrama method significantly the abality of determining intrinsic elements short story than use of conventional method.The effect sociodrama method the abality of determining intrinsic elements short story is 55% while 45% are influenced by other factors.Keywords: Sociodrama method, the abality of determining intrinsic elements short story.